2000
DOI: 10.1103/physreve.62.4393
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the evolutionary minority game

Abstract: We present a theory describing a recently introduced model of an evolving, adaptive system in which agents compete to be in the minority. The agents themselves are able to evolve their strategies over time in an attempt to improve their performance. The theory explicitly demonstrates the self-interaction, or market impact, that agents in such systems experience.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
186
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(186 citation statements)
references
References 15 publications
0
186
0
Order By: Relevance
“…In this context many problems become trivial. For example, consider a situation in which Alice wants to 'teleport' [1] a quantum state, whose identity is known to her, to Bob (this has come to be known as 'remote state preparation' [2][3][4]). If classical information is considered to be free, then no teleportation-type procedure is actually needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this context many problems become trivial. For example, consider a situation in which Alice wants to 'teleport' [1] a quantum state, whose identity is known to her, to Bob (this has come to be known as 'remote state preparation' [2][3][4]). If classical information is considered to be free, then no teleportation-type procedure is actually needed.…”
Section: Introductionmentioning
confidence: 99%
“…Given the unitary operations {u m } n−1 m=0 , we can find an ensemble of states that satisfy Eq. (3). If the number of states in the ensemble is less than n the RSP protocol is useless.…”
Section: Rsp Achieved By Using Minimum Classical Bitsmentioning
confidence: 99%
“…The choice of which type of measurement will be used in certain quantum information protocols, such as remote state preparation [3][4][5] or quantum state discrimination [6], is important. For example, in the case of unambiguous quantum state discrimination [7], Peres [8] showed that the POVMs found by Dieks [9] are actually the ones that minimize the failure probability.…”
Section: Introductionmentioning
confidence: 99%